Análisis de variables causantes de retrasos de obras viales en la Región Caribe (2020)
Delays and cost overruns in construction projects are a constant in the development of these, making the viability of such projects is compromised. For this reason, it is necessary to identify the causes that affect the development of construction applied in Colombia. This research focused on the identification of variables causing delays for road construction projects in the Colombian Caribbean Region, therefore, a literary review was started where the most common variables causing delays and on costs worldwide were identified, national and regional. With the variables already identified, a survey was conducted for professionals in the area of construction of road works, where they expressed their point of view regarding these variables in terms of delay and cost overruns that these entail for the different works and the occurrence and relevance of the themselves. In the end, statistical analyzes were applied to the results of the surveys to establish which variables are the ones that generate the most impacts when building a road work in the Colombian Caribbean Region.